Patriotism, nationalism, and evaluations of the government’s handling of the coronavirus crisis - Zhai, Yida; Lu, Yizhen; Wu, Qidi (Frontiers in Psychology, 2023)
Introduction The COVID-19 pandemic has been accompanied by a global rise of nationalism, and many countries’ responses to the pandemic have further intensified nationalist sentiments. The public is polarized over government policies toward the pandemic. Hence, this study examined the associations of patriotism and nationalism with the support for lockdown policies and evaluations of governmental performance. Methods We recruited 180 participants from one Chinese university. Results Patriotism and nationalism had a direct effect on evaluations of governmental performance. Patriotism also had indirect effects on favorable evaluations of governmental performance through the support of lockdown policies. In addition, this study examined the relationship of threat perception and evaluations of governmental performance in the pandemic. Discussion This relationship was found to be insignificant; however, the interaction effects between threat perception and patriotism on evaluations of governmental performance were significant. The implications of the study results are discussed.